2009
DOI: 10.1203/pdr.0b013e3181b3b1f6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microcirculation as Early Markers for Infection in Preterm Infants—An Observational Prospective Study

Abstract: ABSTRACT:In adults with severe sepsis, the disturbances of the sublingual microcirculation can be quantified with orthogonal polarization spectral imaging. We investigated the cutaneous microcirculation of preterm infants with proven infection (PosInf) and with suspected but unproven infection (NegInf). In 25 infants, orthogonal polarization spectral images were obtained daily, videos of the images were blinded, and analyzed off-line. Functional small vessel density (FSVD) was prospectively calculated from day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 19 publications
1
37
1
1
Order By: Relevance
“…In adults, studies on sublingual microcirculation using OPS imaging in septic patients have shown associations between microcirculatory distress, disease severity and response to therapy 5 7 23. In preterm neonates, Weidlich et al used OPS to identify changes in microcirculation as an early marker of infection 24. The routine clinical use of OPS and SDF is limited by the relatively difficult application and especially the complicated and time-consuming analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, studies on sublingual microcirculation using OPS imaging in septic patients have shown associations between microcirculatory distress, disease severity and response to therapy 5 7 23. In preterm neonates, Weidlich et al used OPS to identify changes in microcirculation as an early marker of infection 24. The routine clinical use of OPS and SDF is limited by the relatively difficult application and especially the complicated and time-consuming analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Top and co-workers reported that such alterations also occur in the buccal mucosa of septic children [59]. In premature neonates with sepsis, microcirculatory alterations were observed in the skin using OPS imaging [58]. Furthermore, neonates with severe respiratory failure have depressed microcirculatory parameters [57].…”
Section: Microcirculation In Disease and The Effects Of Treatmentmentioning
confidence: 99%
“…The microcirculation is the area where the final step of the oxygen transport chain occurs. Observational studies have demonstrated a relation between microcirculatory deterioration over time and the presence of bacterial infections 14 . As deterioration of the peripheral microcirculation is one of the first signs of sepsis in preterm infants, it is generally hypothesised that the peripheral microcirculation can help predict the development of sepsis.…”
Section: Discussionmentioning
confidence: 99%